2018
DOI: 10.3389/fpls.2018.01414
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Homologous Sequences of Saccharum officinarum and Saccharum spontaneum Reveals Independent Polyploidization Events

Abstract: Sugarcane (Saccharum spp. hybrids) is an economically important crop widely grown in tropical and subtropical regions for sugar and ethanol production. However, the large genome size, high ploidy level, interspecific hybridization and aneuploidy make sugarcane one of the most complex genomes and have long hampered genome research in sugarcane. Modern sugarcane cultivars are derived from interspecific hybridization between S. officinarum and S. spontaneum with 80–90% of the genome from S. officinarum and 10–20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…spontaneum, resulting in an octoploid with ten basic sets of chromosomes (2n=8x=80) (Sharma et al, 2018;Vilela et al, 2017;Zhang et al, 2021a). In support of this idea, a recent study which combined these two species to create a mosaic monoploid reference genome for Saccharum hybrid species reported that polyploidization in these species occurred after the divergence from sorghum (Garsmeur et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…spontaneum, resulting in an octoploid with ten basic sets of chromosomes (2n=8x=80) (Sharma et al, 2018;Vilela et al, 2017;Zhang et al, 2021a). In support of this idea, a recent study which combined these two species to create a mosaic monoploid reference genome for Saccharum hybrid species reported that polyploidization in these species occurred after the divergence from sorghum (Garsmeur et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Permitem também localizar regiões codificadores de proteínas e identificar segmentos conservados, possibilitando o estudo dos padrões evolutivos de espécies relacionadas [22,[26][27][28][29]. Pesquisas em genômica comparativa foram reportadas em diversas espécies vegetais, por exemplo, as realizadas entre Brassica oleracea e Arabidopsis thaliana [30], Zea mays e A. thaliana [31], Fragaria e outras espécies do clado das Rosideas [32], Solanum lycopersicum e S. tuberosum [33], Oryza sativa e Ananas comosus [34], Glycine soja e outras 9 espécies de Glicine [35], Saccharum officinarum e S. spontaneum [36], entre outras.…”
Section: Introductionunclassified